Elimination of Health Records: A Patient's Right? (Revista Iberoamericana de Bioética, 2020)
Patients' access to their health data has become a common issue in recent years, raising some ethical issues surrounding privacy and security of access. “The right to be forgotten", that is, the right to allow an individual to request the removal of their health data, is now a possibility, and this poses some new problems. We believe it should not be possible to universalize the right of a patient to erase health data, without evaluating the effects that the elimination of this information may have on the health of certain individuals or populations. The right of an individual to eliminate his health data should be assessed on a case-by-case basis, considering the possible consequences in different ways.
Keywords: right to be forgotten; personal health records; privacy; confidentiality; public health